Factors associated with recent and regular non-use of dental services by students from a university in southeastern Brazil: a cross-sectional study - Rafaela de Oliveira Cunha; Isabel Cristina Gonçalves Leite (BMC, 2022)
Abstract Background Lack of use of dental services can be a risk factor for oral health. In addition to recent visits to dental services, it is important to assess the regularity of use of these services, as well as the motivations for visiting the dentist. There is a gap in literature studies on the patterns of use of oral health services by the young university students. The goal of this study was to assess the factors associated with recent and regular non-use of dental services by young university students, using the Andersen model as a reference. Methods This was a cross-sectional study with 477 university students between 18 and 24 years old, carried out as a web survey, through which predisposing, enabling and need variables were collected, according to the model proposed by Andersen, to test the factors associated with recent and regular non-use of dental services. Bivariate analyses and robust Poisson regression were performed, with estimation of crude and adjusted prevalence ratios, using confidence intervals of 95%. The variables with p < 0.05 remained in the final model. Results The prevalence of recent non-use was of 19.5% (95% CI 16.0-23.3%), and of regular non-use, of 53.5% (95% CI 48.9-58.0%). After the adjusted analysis, the following were found to be associated with the outcome of recent non-use: type of service used (PR = 0.91; 95% CI 0.85-0.98) and perceived need for dental treatment (PR = 0.98; 95% CI 0.97-0.99); and the following variables were associated with regular non-use: father's level of education (PR = 0.86; 95% CI 0.78-0.96), area of study (PR = 1.08; 95% CI 1.02-1.15), reason for last dental appointment (PR = 0.81; 95% CI 0.75-0.88), use of dental services throughout childhood (PR = 0.92; 95% CI 0.86-0.97), self-perceived oral health (PR = 0.86; 95% CI 0.76-0.88), and toothaches over the last 2 years (PR = 0.93; 95% CI 0.87-0.99). Conclusion The motivation for young university students to use dental services are curative treatment needs, not prevention. The results point to the need to implement health prevention and promotion policies in higher education institutions and to expand access to dental services for this young population.